A novel low‐density lipoprotein/fibrinogen apheresis method for chronic limb‐threatening ischemia in patients with poor options for revascularization: A multicenter, single‐arm clinical trial. Issue 2 (16th August 2022) - Kobayashi, Shuzo; Furukawa, Masahide; Ichioka, Shigeru; Horiuchi, Katsumi; Kitano, Ikuro; Fujii, Miki; Ayabe, Shinobu; Tanaka, Rica; Ohura, Norihiko; Ohura, Takehiko
Abstract: Introduction: Low‐density lipoprotein (LDL) apheresis is a treatment option for patients with unhealed chronic limb‐threatening ischemia (CLTI) after revascularization. The newly developed AS‐25 is a direct hemoperfusion‐type apheresis device that differs from conventional LDL apheresis therapy and is designed to specifically adsorb both LDL‐C and fibrinogen. We evaluate the efficacy and safety of AS‐25. Methods: This study included 61 patients whose ulcers failed to heal after revascularization or were ineligible for revascularization. Of these, 50 were undergoing hemodialysis. The primary endpoint was the healing rate of a target lesion of interest (ulcer), using historical data as control. Results: The ulcer healing rate of 45.9% was significantly higher than the historical data. No significant safety concerns were observed. Conclusions: AS‐25 was effective in healing ulcers and preventing major amputation even in CLTI refractory patients on hemodialysis, thus showing potential clinical applicability and high significance. Clinical Trial Registration: UMIN study ID UMIN000020336.